Interest in Skin Cancer in Urban Populations: A Retrospective Analysis of Google Search Terms in Nine Large German Cities - Linda Tizek; Maximilian C. Schielein; Melvin Rüth; Rolf-Markus Szeimies; Wolfgang G. Philipp-Dormston; Stephan A. Braun; Christine Hecker; Bernadette Eberlein; Tilo Biedermann; Alexander Zink (Medical Journals Sweden, 2019)
Skin cancer is a major public health issue, which could be reduced through prevention programmes. However, prevention utilization is not very prevalent. It is therefore important to understand individuals' interest in skin cancer. Google AdWords Keyword Planner was used to identify the search volume of terms relating to skin cancer in 9 German cities between July 2014 and June 2018. From a total of 1,203 identified keywords, 1,047 search terms were related to skin cancer, which had a search volume of 3,460,980 queries for the study period. Most terms referred to "identifying skin cancer". For melanoma, the number of Google searches per 100,000 inhabitants correlated with the cancer registry data for melanoma incidence rates (men: r = 0.810, women: r = 0.569). Assessment of this data for the different cities further enabled identification of regional variations, which could help to identify areas with a high need for targeted prevention campaigns.